1996
DOI: 10.1176/jnp.8.2.181
|View full text |Cite
|
Sign up to set email alerts
|

A survey study of neuropsychiatric complaints in patients with Graves' disease

Abstract: One hundred thirty-seven patients with treated Graves' disease completed a questionnaire pertaining to neuropsychiatric complaints. Psychiatric symptoms, especially anxiety and irritability, were common prior to treatment of hyperthyroidism. These complaints appeared to result in delays in seeking treatment as well as delays in receiving appropriate diagnosis. Subjects reported significantly worse memory, attention, planning, and productivity while hyperthyroid than prior to becoming hyperthyroid, and, althoug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
21
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(26 citation statements)
references
References 11 publications
3
21
0
2
Order By: Relevance
“…The present findings are interesting because they suggest that zinc may play a role in a wide range of psychiatric disorders. Among patients with thyrotoxicosis, some individuals develop anxiety, others develop depression or psychosis, and still others, do not develop psychiatric disorders at all [42]. We find the same pattern in for example patients with hyperparathyroidism [43], [44] and in patients with low levels of vitamin B12 [45].…”
Section: Discussionsupporting
confidence: 67%
“…The present findings are interesting because they suggest that zinc may play a role in a wide range of psychiatric disorders. Among patients with thyrotoxicosis, some individuals develop anxiety, others develop depression or psychosis, and still others, do not develop psychiatric disorders at all [42]. We find the same pattern in for example patients with hyperparathyroidism [43], [44] and in patients with low levels of vitamin B12 [45].…”
Section: Discussionsupporting
confidence: 67%
“…It is well known that a diversity of psychiatric symptoms can occur in connection with various medical conditions. Some patients with thyrotoxicosis develop depression, others develop anxiety or psychosis, and some do not develop psychiatric disorders at all [40]. The same pattern is found in patients with hyperparathyroidism [41] and in patients with low levels of vitamin B12 [42].…”
Section: Discussionmentioning
confidence: 93%
“…They are often found in patients with chronic somatic diseases, among these thyroid dysfunction [2]. Hypothyroidism has been linked to depression [2,3,4,5,6] but increased prevalence of anxiety and depression is also found in hyperthyroidism [7], particularly in the early phase of Graves' disease [8,9,10,11], compared with the general population or compared with patients with other chronic thyroid diseases [2,12,13]. It remains unclear to which extent anxiety and depression relate to chronic disease as such, or whether it is uniquely tied to hyperthyroidism.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies of hyperthyroid patients found that symptoms of anxiety and depression disappeared within months of starting anti-thyroid drug treatment [2,14,15], indicating that increased levels of thyroid hormones may contribute to anxiety and depression [2,16,17]. Others found that symptoms persisted despite successful anti-thyroid drug treatment [11,18,19,20,21], indicating that anxiety and depression might be related to other aspects of hyperthyroidism, such as thyroid autoimmunity, rather than thyroid hormone status. Elevated levels of thyroid peroxidase antibodies (TPOAb) have been directly related to anxiety and depression in some [19,22,23] but not in all studies [24].…”
Section: Introductionmentioning
confidence: 99%